1985
DOI: 10.1902/jop.1985.56.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Langerhans Cells in Human Gingival Epithelium

Abstract: The purpose of this study was to qualitatively compare three recent techniques of Langerhans cells detection in oral epithelium and to quantitatively compare Langerhans cells in clinically normal and clinically inflamed human gingival biopsies. Eleven subjects were selected who displayed chronic periodontitis and moderate gingival inflammation. A quadrant associated with clinically inflamed tissues was not treated, while the remaining teeth were scaled and root-planed. Two gingival biopsies were taken: clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
4

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 39 publications
2
20
1
4
Order By: Relevance
“…The literature shows divergent results regarding the number of DCs in patients with periodontal diseases. Some studies 10,12,14,15 reported an increased quantity of these cells in patients with chronic gingivitis and periodontitis compared to healthy periodontal tissues, whereas other studies 16,17 presented a decreased number according to the severity of the periodontal disease. In addition, no quantitative change in periodontitis compared to gingivitis and healthy periodontal tissues 18 has been reported.…”
mentioning
confidence: 99%
“…The literature shows divergent results regarding the number of DCs in patients with periodontal diseases. Some studies 10,12,14,15 reported an increased quantity of these cells in patients with chronic gingivitis and periodontitis compared to healthy periodontal tissues, whereas other studies 16,17 presented a decreased number according to the severity of the periodontal disease. In addition, no quantitative change in periodontitis compared to gingivitis and healthy periodontal tissues 18 has been reported.…”
mentioning
confidence: 99%
“…The presence of numerous CD1a+ Langerhans cells was noted in the epithelium with no difference between the healthy/gingivitis and periodontitis group (Gemmell et al 2003). Five times as many CD1a+ Langerhans cells have been shown in clinically inflamed gingival epithelium compared with numbers in the same patients following periodontal treatment (DiFranco 1985). While T cells exhibit immunoregulatory features via T-helper 1 and T-helper 2 subsets, B cells upon activation transform into antibody producing plasma cells.…”
Section: T and B Cellsmentioning
confidence: 93%
“…These foci develop in response to pathogen-associated molecular patterns. [13] In chronic adult periodontitis, mature CD83+ DCs form immune conjugates with CD4+ T cells in the oral lymphoid foci. [114]…”
Section: Langerhans Cells In Different Pathological Conditionsmentioning
confidence: 99%